ECONOMIC EVALUATION OF ORNAMENTAL FISH TRADE IN NIGERIA (2013)
Nigeria has over three thousand Ornamental Fish species and the potential of being one of the leading exporters. In spite of the flourishing trade of Ornamental Fish worldwide however, her extant share of the trade is below 5% of Africa's total contribution. In addition, there is paucity of information on the marketing factors influencing Ornamental Fish trade in Nigeria. The marketing channel and factors influencing Ornamental Fish trade in Nigeria were therefore investigated. A two-stage sampling technique was used to select Ornamental Fish traders. The traders were stratified into fishermen, middlemen and exporters, from where 50% sampling from each stratum was carried out. A total sample size of 196 Ornamental Fish traders located in 14 producing states of Nigeria (Lagos, Ogun, Edo, Delta, Rivers, Bayelsa, Abia, Cross River, Akwa Ibom, Kano, Benue, Ondo, Niger and Nassarawa) was used for the study. This includes 139 fishermen, 40 middlemen and 17 exporters. Data were collected on personal characteristics of respondents, sources of fund, types of fish holding facilities, transportation and labour costs, quantity and types of and cost of Ornamental Fish supplied, and revenue generated on quarterly basis using structured questionnaire. Data were analyzed using descriptive statistics, gross margin and multiple regression models at p=0.05. Male respondents were 91.3%; this includes 72.0%, 19.6% and 8.4% of fishermen, middlemen and exporters respectively. The mean ages of the fishermen, middlemen and exporters were 47.3 ± 1.2, 44.5 ± 1.5, and 42.6 ± 2.3 years respectively. Respondents with no formal education, primary school leaving certificate, secondary school certificate, and tertiary education were 37.3%, 32.3%, 23.5% and 6.1% respectively. The Ornamental Fish marketing channel involved fish sales from fishermen to middlemen who finally sell to consumers. Gross margin of the middlemen were highest in the first (N9,288,876) and third (N4,054,679) quarters, while the gross margin of the exporters were highest in the second (N3,485,961) and fourth (N4,088,522) quarters of the year. Exporters had the highest average marketing efficiency (85.1%) throughout the four quarters of the year. Factors that significantly influenced the supply of Ornamental Fish were start-up capital (? = 0.98) and membership of association (? = 0.32). Supply of fish by middlemen were significantly influenced by international price (? = -0.61), membership of association (? = -1.33), and educational qualification (? = 1.03). Only capital (? = 0.00) had significant influence on exporters demand for Ornamental Fish. Lack of capital and seasonality of fish species (100.0%) were the major constraints to Ornamental Fish trade. The trade could be a source of foreign exchange earnings for Nigeria if fishermen associations are empowered and traders have access to start-up capital to expand their business. Investment in the breeding and research on seasonal species will also be required to sustain the industry.